ATP1A2 Mutations in Migraine: Seeing through the Facets of an Ion Pump onto the Neurobiology of Disease - Friedrich, Thomas; Tavraz, Neslihan N.; Junghans, Cornelia (Frontiers in Physiology, 2016)
Mutations in four genes have been identified in familial hemiplegic migraine (FHM), from which CACNA1A (FHM type 1) and SCN1A (FHM type 3) code for neuronal voltage-gated calcium or sodium channels, respectively, while ATP1A2 (FHM type 2) encodes the α2 isoform of the Na+,K+-ATPase’s catalytic subunit, thus classifying FHM primarily as an ion channel / ion transporter pathology. FHM type 4 is attributed to mutations in the PRRT2 gene, which encodes a proline-rich transmembrane protein of as yet unknown function. The Na+,K+-ATPase maintains the physiological gradients for Na+ and K+ ions and is, therefore, critical for the activity of ion channels and transporters involved neuronal excitability, neurotransmitter uptake or Ca2+ signaling. Strikingly diverse functional abnormalities have been identified for disease-linked ATP1A2 mutations which frequently lead to changes in the enzyme’s voltage-dependent properties, kinetics, or apparent cation affinities, but some mutations are truly deleterious for enzyme function and thus cause full haploinsufficiency. Here, we summarize structural and functional data about the Na+,K+-ATPase available to date and an overview is provided about the particular properties of the α2 isoform that explain its physiological relevance in electrically excitable tissues. In addition, current concepts about the neurobiology of migraine, the correlations between primary brain dysfunction and mechanisms of headache pain generation are described, together with insights gained recently from modeling approaches in computational neuroscience. Then, a survey is given about ATP1A2 mutations implicated in migraine cases as documented in the literature with focus on mutations that were described to completely destroy enzyme function, or lead to misfolded or mistargeted protein in particular model cell lines. We also discuss whether or not there are correlations between these most severe mutational effects and clinical phenotypes. Finally, perspectives for future research on the implications of Na+,K+-ATPase mutations in human pathologies are presented.